Economy responses to stride frequency variations during diagonal stride treadmill roller-skiing - Newbury-Asmus, V.; Watts, P. B. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: It has been established that variations in stride length and associated stride frequency can influence oxygen consumption and energy expenditure during locomotive activities such as running. Whether this effect occurs in cross-country skiing has not been reported. The purpose of this study was to observe the effect of stride frequency Variation on heart rate (HR), oxygen consumption (VO2), and rating of perceived exertion (RPE) during constant velocity treadmill roller-skiing.